Assuring Quality in Pharmacy Education During a Time of Crisis - Engle, Janet P. (Am J Pharm Educ, 2020)
The COVID-19 pandemic has disrupted all facets of pharmacy education, including accreditation and certification activities. In a very short period of time, Doctor of Pharmacy (PharmD) programs and pharmacy technician programs had to convert to teaching classes online, experiential education sites had to figure out how to train student pharmacists and pharmacy technicians while ensuring their safety, continuing pharmacy education providers had to move their in-person courses online, and the Accreditation Council for Pharmacy Education (ACPE) had to postpone accreditation site visits. Given the challenges faced by our constituencies, the ACPE implemented processes and suggested solutions that stayed within the boundaries of the standards while at the same time allowing flexibility so that organizations could achieve their educational outcomes even given the constraints produced by the pandemic.